Opening legations: Japan’s first resident minister and the diplomatic corps in Europe - Cobbing, Andrew (Taylor & Francis (Routledge), 2017)
This analysis shows how Japanese legations, first established in Europe during the 1870s, were not just symbolic gestures but played a key role in the Meiji government’s quest for international recognition. The concept of resident ambassador was unfamiliar beyond the European world, so the transition from sending visiting envoys to establishing permanent missions was a pivotal stage. Here a comparative framework gauges the importance of Japan’s new strategy within the context of similar experiments by states such as the Ottoman Empire, Persia, and subsequently China and Siam. The case of Sameshima Naonobu, Japan’s first resident minister in Europe, highlights the cultural barriers the Japanese faced. Assisted by Frederick Marshall, an Englishman at the Japanese Legation in Paris, Sameshima’s research on the mysteries encoded in this particular social universe offers some insight on the nature of the diplomatic corps in Europe.